Upaya membentuk karakter mahasiswa berbasis masjid kampus di Fakultas Ilmu Keolahragaan Universitas Negeri Makassar - Muhammadong Muhammadong; Wahyudin Wahyudin; Saharullah Saharullah (Seminar Nasional LP2M UNM, 2019)
Character education is a solution to overcome the problems faced by the government. The character formation is the dream of every university so that it can produce the students who have integrity so that they are not easily affected in anarchic actions. The big hope in creating the character of the students of the Faculty of Sport Sciences, Universitas Negeri Makassar is to make campus mosques as a place to develop the academic insights which contain the Islamic nuances. So that the Faculty of Sports Science can produce the students who have authority and integrity. Religious studies conducted by the students in the campus mosques are extracurricular activities that can increase religious insight so that they can implement the Islamic teachings. The campus mosques are not only made as a place to worship, but also as a place to study with religious studies, religious discussions, and da'wah practices so that the students can have a good character.